Defective glutamate and K+ clearance by cortical astrocytes in familial hemiplegic migraine type 2 - Clizia Capuani; Marcello Melone; Angelita Tottene; Luca Bragina; Giovanna Crivellaro; Mirko Santello; Giorgio Casari; Fiorenzo Conti; Daniela Pietrobon (EMBO Molecular Medicine)
Abstract Migraine is a common disabling brain disorder. A subtype of migraine with aura (familial hemiplegic migraine type 2: FHM2) is caused by loss‐of‐function mutations in α2 Na+,K+ ATPase (α2 NKA), an isoform almost exclusively expressed in astrocytes in adult brain. Cortical spreading depression (CSD), the phenomenon that underlies migraine aura and activates migraine headache mechanisms, is facilitated in heterozygous FHM2‐knockin mice with reduced expression of α2 NKA. The mechanisms underlying an increased susceptibility to CSD in FHM2 are unknown. Here, we show reduced rates of glutamate and K+ clearance by cortical astrocytes during neuronal activity and reduced density of GLT‐1a glutamate transporters in cortical perisynaptic astrocytic processes in heterozygous FHM2‐knockin mice, demonstrating key physiological roles of α2 NKA and supporting tight coupling with GLT‐1a. Using ceftriaxone treatment of FHM2 mutants and partial inhibition of glutamate transporters in wild‐type mice, we obtain evidence that defective glutamate clearance can account for most of the facilitation of CSD initiation in FHM2‐knockin mice, pointing to excessive glutamatergic transmission as a key mechanism underlying the vulnerability to CSD ignition in migraine.